A Novel Finding of an HLA Allele’s and a Haplotype’s Relationship with SARS-CoV-2 Vaccine-Associated Subacute Thyroiditis - Melisa Sahin Tekin; Goknur Yorulmaz; Emel Yantir; Eren Gunduz; Ertugrul Colak (Vaccines, 2022)
Subacute thyroiditis (SAT) is a thyroid disease associated with viral infections. Its relationship with major histocompatibility complex (MHC) antigens was shown before. SAT cases triggered by different types of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines have been reported. In this study, human leukocyte antigen (HLA) genotypes of 27 SAT patients (13 vaccine-associated (V-SAT) and 14 non-SARS-CoV-2-infection non-vaccine-associated (non-V-SAT)) were compared with those of 362 healthy donors. HLA analyses were performed with low-resolution DNA-based sequence-specific oligonucleotide or sequence-specific primer methods. Statistical analyses were performed using IBM SPSS Statistics 25 and Stata/MP 14.1 with the hapipf function. Allele and haplotype frequencies were estimated by PyPop and gene[RATE] tool programs. The allele frequencies of HLA-A*11, HLA-B*35, and HLA-C*04 were higher in the patient groups. Both the allele frequency of HLA-A*11 and the haplotype frequency of A*11-B*35-C*04 were higher in the V-SAT group. The A*11-B*35-C*04 haplotype, including all three loci of MHC class I genes, is shown to be associated with the disease for the first time, especially in the V-SAT group. This finding will contribute to a better understanding of the etiopathogenesis of vaccine-associated SAT and the role of HLA genotypes in the functioning mechanisms of the SARS-CoV-2 vaccines.